In vitro antiproliferative/cytotoxic activity on cancer cell lines of a cardanol and a cardol enriched from Thai Apis mellifera propolis - Teerasripreecha, Dungporn (BioMed Central, 2012)
BACKGROUND: Propolis is a complex resinous honeybee product. It is reported to display diverse bioactivities, such as antimicrobial, anti-inflammatory and anti-tumor properties, which are mainly due to phenolic compounds, and especially flavonoids. The diversity of bioactive compounds depends on the geography and climate, since these factors affect the floral diversity. Here, Apis mellifera propolis from Nan province, Thailand, was evaluated for potential anti-cancer activity. METHODS: Propolis was sequentially extracted with methanol, dichloromethane and hexane and the cytotoxic activity of each crude extract was assayed for antiproliferative/cytotoxic activity in vitro against five human cell lines derived from duet carcinoma (BT474), undifferentiated lung (Chaco), liver hepatoblastoma (Hep-G(2)), gastric carcinoma (KATO-III) and colon adenocarcinoma (SW620) cancers. The human foreskin fibroblast cell line (Hs27) was used as a non-transformed control. Those crude extracts that displayed antiproliferative/cytotoxic activity were then further fractionated by column chromatography using TLC-pattern and MTT-cytotoxicity bioassay guided selection of the fractions. The chemical structure of each enriched bioactive compound was analyzed by nuclear magnetic resonance and mass spectroscopy. RESULTS: The crude hexane and dichloromethane extracts of propolis displayed antiproliferative/cytotoxic activities with IC(50 )values across the five cancer cell lines ranging from 41.3 to 52.4 μg/ml and from 43.8 to 53.5 μg/ml, respectively. Two main bioactive components were isolated, one cardanol and one cardol, with broadly similar in vitro antiproliferation/cytotoxicity IC(50 )values across the five cancer cell lines and the control Hs27 cell line, ranging from 10.8 to 29.3 μg/ml for the cardanol and < 3.13 to 5.97 μg/ml (6.82 - 13.0 μM) for the cardol. Moreover, both compounds induced cytotoxicity and cell death without DNA fragmentation in the cancer cells, but only an antiproliferation response in the control Hs27 cells However, these two compounds did not account for the net antiproliferation/cytotoxic activity of the crude extracts suggesting the existence of other potent compounds or synergistic interactions in the propolis extracts(.) CONCLUSION: This is the first report that Thai A. mellifera propolis contains at least two potentially new compounds (a cardanol and a cardol) with potential anti-cancer bioactivity. Both could be alternative antiproliferative agents for future development as anti-cancer drugs.